Efektivitas Rebusan Biji Ketumbar dan Rebusan Daun Sirsak Terhadap Masalah Keputihan Pada Wus di Wilayah Kerja Puskesmas Sukatani Kabupaten Bekasi - Narmi Nurmayani; Resi Galaupa (Universitas Malahayati Lampung, 2024)
ABSTRACT Women of childbearing age often experience vaginal discharge. Treatment therapy for vaginal discharge can use non-pharmacological treatments, one of which is a decoction of coriander seeds and soursop leaves. The incidence of leucorrhoea in the working area of the Sukatani Health Center, Bekasi Regency, has increased every year. To know the effectiveness of coriander seed decoction and soursop leaf decoction for leucorrhoea problems in WUS in the Working Area of the Sukatani Health Center, Bekasi Regency. Quasi-experimental design with pretest-posttest design and control group design. The samples were taken from 34 women of childbearing age who experienced vaginal discharge in January–February 2023 using a purposive sampling technique. The intervention was given once a day for 7 days. Bivariate analysis used paired simple t tests and independent t tests. The results of univariate research on average vaginal discharge problems in WUS before administration of coriander seed decoction were 6.59 and 3.41, respectively. The average vaginal discharge problem in WUS before administration of soursop leaf decoction was 6.53 and after 4.71. The bivariate results of the paired simple t test were 0.000, and the independent t test obtained a p value of 0.000. Giving coriander seed decoction is more effective against leucorrhoea problems in WUS than soursop leaf decoction. Women of childbearing age are expected to improve their behavior in protecting the female area and to be able to take non-pharmacological treatments, one of which is using coriander seed decoction and soursop leaf decoction. Keywords: Decoction of Coriander Seeds, Decoction of Soursop Leaves, Leucorrhoea of Women of Reproductive Age ABSTRAK Wanita usia subur sering mengalami keputihan, terapi pengobatan untuk keputihan dapat menggunakan pengobatan non farmakologi salah satunya dengan rebusan biji ketumbar dan rebusan daun sirsak. Kejadian keputihan di Wilayah Kerja Puskesmas Sukatani Kabupaten Bekasi setiap tahunnya mengalami peningkatan. Mengetahui efektivitas rebusan biji ketumbar dan rebusan daun sirsak terhadap masalah keputihan pada WUS di Wilayah Kerja Puskesmas Sukatani Kabupaten Bekasi. Quasy eksperimental desain dengan rancangan pretest-posttest with control group design. Sampel adalah wanita usia subur yang mengalami keputihan pada bulan Januari-Pebruari tahun 2023 sebanyak 34 sampel dengan teknik purposive sampling. Intervensi diberikan 1 x sehari 250g selama 7 hari. Analisis bivariat menggunakan uji paired simple t test dan t test independent. Hasil penelitian univariat rata-rata masalah keputihan pada WUS sebelum pemberian rebusan biji ketumbar 6,59 dan sesudah 3,41. Rata-rata masalah keputihan pada WUS sebelum pemberian rebusan daun sirsak 6,53 dan sesudah 4,71. Hasil penelitian bivariat uji paired simple t test sebesar 0,000 dan uji t test independent didapatkan nilai p value = 0,000. Pemberian rebusan biji ketumbar lebih efektif terhadap masalah keputihan pada WUS dibandingkan rebusan daun sirsak. Wanita usia subur diharapkan dapat meningkatkan perilakunya dalam menjaga daerah kewanitaan serta dapat melakukan pengobatan dengan menggunakan nonfarmakologi salah satunya menggunakan rebusan biji ketumbar dan rebusan daun sirsak. Kata Kunci: Rebusan Biji Ketumbar, Rebusan Daun Sirsak, Keputihan Wanita Usia Subur